Retropharyngeal lymph node involvement in human papillomavirus–associated oropharyngeal squamous cell carcinoma. (30th July 2015) - Baxter, Michael; Chan, Jason Y. K.; Mydlarz, Wojciech K.; Labruzzo, Salvatore V.; Kiess, Ana; Ha, Patrick K.; Nafi, Aygun; Nishant, Agrawal
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The purpose of this study was to retrospectively review patients with human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma (OPSCC) for the presence of retropharyngeal lymph nodes (RPLNs) prior to treatment using positron emission tomography/computed tomography (PET/CT), and to determine if the presence of RPLNs is of utility in predicting outcomes. Study Design Retrospective review of patient data from a single institution. Methods Two hundred thirty patients with a diagnosis of HPV‐associated OPSCC were identified from 2002 to 2013. The presence of RPLNs was determined primarily from findings on PET/CT as reviewed in a standardized fashion by two neuroradiologists. Results Of the 230 patients, 165 had pretreatment PET/CT imaging available for review. There were a total of 16 patients (9.70%) with evidence of RPLNs. Among patients positive for RPLNs pretreatment, with an average follow‐up of 2 years, there was a 5.2‐times greater odds of having recurrence or death (31.3% vs. 8.1%, P = .004). When T and N stage were adjusted for with multiple regression, there was no significant association between RPLN status and recurrence free survival. Conclusions This is a unique investigation utilizing PET/CT to classify RPLN status in HPV‐associated OPSCC. RPLNs were relatively common in our HPV‐associated OPSCC cohort at 9.70%, at the low end of the quoted positivity of 10% to 27% in all OPSCC. A combination of PET/CT is useful in identifying RPLNs. Prospective investigation will be needed to determine the sensitivity and specificity of PET/CT in identifying RPLNs, and the precise impact of RPLNs on HPV‐associated OPSCC treatment and outcomes. Level of Evidence 4. Laryngoscope, 125:2503–2508, 2015